Penetapan Peraturan Pemerintah Pengganti Undang-Undang di Dewan Perwakilan Rakyat Pada Masa Reses - Nisfu Ramadhan, Farhan Adhitiya; Perdana, Surya (LPPM Universitas Ekasakti Padang, 2024)
This research discusses government regulations in lieu of laws in the people's representative council during the recess. Through a juridical approach, this research explores the constitutional basis, time period and stipulation of government regulations in lieu of law for the people's representative council during the recess. The results of the research show that there is no provision for a time period for enacting government regulations in lieu of laws depending on